Advanced DC/DC converters. - Luo, Fang Lin, ....-; Ye, Hong, ....- (Boca Raton : CRC, 2004)
Samenvatting:Provides a systematic, practical treatment of DC/DC converters, fromtheir classical roots to the state of the art" Contains information on the latest techniques including voltage-lift,super-lift, and the new cascade prototypes" Introduces more than 100 topologies developed by the authors" Illustrates EMI/EMC reduction and various DC voltage sources" Presents theory and applications using hundreds of figures,discussions, and examplesDC/DC conversion techniques have undergone rapid development in recentdecades. With the pioneering work of authors Fang Lin Luo and Hong Ye,DC/DC converters have now been sorted into their six generations, and bya rough count, over 500 different topologies currently exist, with morebeing developed each year.Advanced DC/DC Converters offers a concise, practical presentation ofDC/DC converters, summarizing the spectrum of conversion technologies andpresenting many new ideas and more than 100 new topologies. The treatmentbegins with background material on DC/DC conversion and discussions onvoltage lift and super-lift converters. It then proceeds through eachgeneration, including the groundbreaking sixth generation--convertersdeveloped by the authors that can be cascaded for high voltage transfergain.More than 320 figures, 60 tables, and 500 formulae allow you to moreeasily grasp the overall structure of advanced DC/DC converters, providefast access to precise data, and help you quickly determine the values ofyour own circuit components. Nowhere else in the literature are DC/DCconverters so logically sorted and systematically introduced. Nowhereelse can you find detailed information on prototype topologies thatrepresent a major contribution to modern power engineering.
Keywords: Elektronische voedingen; Gelijkstroom-gelijkstroom omvormers; Omzetters